Catalytic hydrogenolysis of lignin and model compounds over highly dispersed Ni-Ru/Al2O3 without additional H2. (15th October 2022) - Wang, Hai-Tao; Li, Zhan-Ku; Yan, Hong-Lei; Lei, Zhi-Ping; Yan, Jing-Chong; Ren, Shi-Biao; Wang, Zhi-Cai; Kang, Shi-Gang; Shui, Heng-Fu
Highlights: A highly dispersed Ni-Ru/Al2 O3 based on layered double hydroxide was prepared. Model compounds can be completely transformed into monomers below 150 °C without H2 . The transfer of electrons from Ni to Ru is beneficial to form active hydrogen on the catalyst. Isopropanol as hydrogen source exhibits much better performance than other solvents. Apparent activation energies increase in the order: α-O-4 (90.6 kJ/mol) < β-O-4 (126.7 kJ/mol) < 4-O-5 (172.2 kJ/mol). Abstract: Selective hydrogenolysis of lignin is an attractive strategy for valorizing lignin to fuels/value-added chemicals and developing novel and highly active heterogeneous catalysts is crucial. Herein, a highly dispersed Ni-Ru/Al2 O3 catalyst prepared by a coprecipitation method using layered double hydroxide as precursor was reported. Various lignin model compounds were used to evaluate the catalyst activity. The results show that all the model compounds can be completely transformed into arenes and phenol below 150 °C using isopropanol as hydrogen source, and the latter was easily reduced to cyclohexanol. Kinetics study reveals that apparent activation energies increase in the order: benzyl phenyl ether (90.6 kJ/mol) < phenethoxybenzene (126.7 kJ/mol) < diphenyl ether (172.2 kJ/mol). 2D HSQC NMR analysis exhibits that most of C–O linkages in lignin were cleaved during hydrogenolysis over Ni-Ru/Al2 O3 . The results indicate that the bimetallic Ni-Ru catalyst has a high activity for catalyzing hydrogenolysis of lignin and model compounds. The catalyst was characterized with multiple tools. The results suggest that Ni and Ru nanoparticles in the catalyst are highly dispersed and a strong interaction exists between Ni and Ru, which should be responsible for promoting the hydrogenolysis of lignin and model compounds.